Intervensi Militer Indonesia di Timor Portugis 7 Desember 1975: Analisis Kebijakan Luar Negeri pada Level Sistem Internasional, Politik Domestik, dan Individu - Arif, Muhamad (Global: Jurnal Politik Internasional, 2013)
The focus of this study is on Indonesia's option to conduct military intervention as its foreign policy in Timor Portugis on 7 December 1975. The purpose of this study is to identify factors that influence the government of Indonesia to choose military intervention as in the case of Portuguese Timor. This study uses qualitative approach with data gathered from primary as well as secondary sources and, then, analyzed using descriptive-analytical method. This study concludes that the option to conduct military intervention to Timor Portugis on 7 December 1975 is due to three reasons, i.e.: (1) suportive policies of interested countries, (2) political interaction between foreign policy-making actors in Indonesia, and (3) the personality of President Suharto.